2019
DOI: 10.3324/haematol.2018.214155
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic syndrome-associated spliceosome gene mutations enhance innate immune signaling

Abstract: Myelodysplastic syndrome-associated spliceosome gene mutations enhance innate immune signaling Genes encoding spliceosome components including SF3B1, U2AF1, and SRSF2, are frequently somatically mutated in myelodysplastic syndromes (MDS), other hematologic malignancies, and solid tumors. 1 Typically these are mutually exclusive, heterozygous, missense, hotspot mutations that result in neomorphic or gain-offunction splicing phenotypes. These mutations alter splicing of many genes; however, overlap among the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 21 publications
3
43
1
Order By: Relevance
“…While these are essential splicing factors, inhibition at around the 80% level weakened LPS-induced inflammatory cytokine production without affecting cell viability (12,44,45). This weakened response to LPS was caused, in part, by increased production of MyD88-S when the spliceosome was inhibited (12,44,45). We further showed that moderate inhibition of the spliceosome had relatively specific effects,…”
Section: Myd88 Is Sensitized To Undergo Alternative Splicing To Produmentioning
confidence: 69%
See 2 more Smart Citations
“…While these are essential splicing factors, inhibition at around the 80% level weakened LPS-induced inflammatory cytokine production without affecting cell viability (12,44,45). This weakened response to LPS was caused, in part, by increased production of MyD88-S when the spliceosome was inhibited (12,44,45). We further showed that moderate inhibition of the spliceosome had relatively specific effects,…”
Section: Myd88 Is Sensitized To Undergo Alternative Splicing To Produmentioning
confidence: 69%
“…We have previously shown that inhibition of core components of the spliceosome (SF3A1, SF3A2, SF3A3, SF3B1, or U2AF1) weakens the response to LPS in mouse and/or human macrophages (12,44,45). These core spliceosome factors all bind to the 3' end of introns to facilitate pre-mRNA splicing (46)(47)(48)(49).…”
Section: Myd88 Is Sensitized To Undergo Alternative Splicing To Produmentioning
confidence: 99%
See 1 more Smart Citation
“…However, considering the involvement of CtIP, described here, and BRCA1 (Savage et al, 2014) in RNA splicing, maybe the cancer connection should be revisited on the light of those novel roles. Conversely, recent studies have detected recurrent mutations in components of the spliceosome in myelodysplastic syndromes (Pollyea et al, 2019; Shiozawa et al, 2018), renal cell carcinoma (Verma and Das, 2018; Yang et al, 2017), chronic lymphocytic leukaemia (Agrawal et al, 2017; Maleki et al, 2019), lung adenocarcinoma (Kim et al, 2018; Mao et al, 2019), breast cancer (Gokmen-Polar et al, 2019; Zhao et al, 2019) or pancreatic cancer (Tian et al, 2015; Zhou et al, 2017). Moreover, alterations in expression of splicing factors, including SF3B, can derive in various types of cancers (Alsafadi et al, 2016; Goswami et al, 2014; Maguire et al, 2015; Zheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Smith et al (76) found that the expression of a longer isoform of IRAK4 (IRAK4-L), which is associated with enhanced activation of NF-kB and leukemic transformation, is mediated by mutant forms of the splicing factor U2 small nuclear RNA auxiliary factor 1 (U2AF1). Similarly, Alper et al (77)(78)(79) showed that inhibition of spliceosome genes reduces inflammatory cytokine production in response to TLR agonists, and conversely, expression of MDS-associated spliceosome mutations (involving splicing factors U2AF1, SF3B1, or SRSF2) enhances NF-κB activity and cytokine production by K562 myeloid leukemia cells following TLR stimulation. Mechanistically, the spliceosome mutations alter the splicing of genes that regulate TLR signaling and promote NF-κB activation, including MAP3K7 and CASP8 (77).…”
Section: Tlr Expression and Signaling Is Increased In Patients With Myelodysplastic Syndromes (Mds) And Is Associated With Disease Severimentioning
confidence: 97%